Mast Cell Stabilization Alleviates Acute Lung Injury after Orthotopic Autologous Liver Transplantation in Rats by Downregulating Inflammation - Zhang, Ailan; Chi, Xinjin; Luo, Gangjian; Hei, Ziqing; Xia, Hua; Luo, Chenfang; Wang, Yanling; Mao, Xiaowen; Xia, Zhengyuan (PLOS ONE, 2013)
Background Acute lung injury (ALI) is one of the most severe complications after orthotopic liver transplantation. Amplified inflammatory response after transplantation contributes to the process of ALI, but the mechanism underlying inflammation activation is not completely understood. We have demonstrated that mast cell stabilization attenuated inflammation and ALI in a rodent intestine ischemia/reperfusion model. We hypothesized that upregulation of inflammation triggered by mast cell activation may be involve in ALI after liver transplantation. Methods Adult male Sprague–Dawley rats received orthotopic autologous liver transplantation (OALT) and were executed 4, 8, 16, and 24 h after OALT. The rats were pretreated with the mast cell stabilizers cromolyn sodium or ketotifen 15 min before OALT and executed 8 h after OALT. Lung tissues and arterial blood were collected to evaluate lung injury. β-hexosaminidase and mast cell tryptase levels were assessed to determine the activation of mast cells. Tumor necrosis factor α (TNF-α), interleukin (IL)-1β and IL-6 in serum and lung tissue were analyzed by enzyme-linked immunosorbent assay. Nuclear factor-kappa B (NF-κB) p65 translocation was assessed by Western blot. Results The rats that underwent OALT exhibited severe pulmonary damage with a high wet-to-dry ratio, low partial pressure of oxygen, and low precursor surfactant protein C levels, which corresponded to the significant elevation of pro-inflammatory cytokines, β-hexosaminidase, and tryptase levels in serum and lung tissues. The severity of ALI progressed and maximized 8 h after OALT. Mast cell stabilization significantly inhibited the activation of mast cells, downregulated pro-inflammatory cytokine levels and translocation of NF-κB, and attenuated OALT-induced ALI. Conclusions Mast cell activation amplified inflammation and played an important role in the process of post-OALT related ALI.